2017
DOI: 10.1080/08927014.2017.1383400
|View full text |Cite
|
Sign up to set email alerts
|

A self-assembled clavanin A-coated amniotic membrane scaffold for the prevention of biofilm formation by ocular surface fungal pathogens

Abstract: Amniotic membrane (AM) is frequently used in ophthalmologic surgery for rapid ocular surface reconstruction. Sometimes it may create a major problem with associated infections after biofilm formation over the membrane. To overcome this problem, AM was coated with the antimicrobial peptide clavanin A. The antifungal activity of clavanin A in the native and self-assembled form was determined against the common ocular surface pathogens Candida albicans, Aspergillus fumigatus, Alternaria sp. and Fusarium sp. Biofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In addition to destruction of membrane, other modes of action have also been reported. For instance, in neutral pH, clavanin A adopts the membrane permeation mode of α-helical peptide [ 147 ]. But in slightly acidic pH, it induces cell death by acting proteins on the membrane that maintain a stable pH gradient.…”
Section: Mechanism Of Action Of Ampsmentioning
confidence: 99%
“…In addition to destruction of membrane, other modes of action have also been reported. For instance, in neutral pH, clavanin A adopts the membrane permeation mode of α-helical peptide [ 147 ]. But in slightly acidic pH, it induces cell death by acting proteins on the membrane that maintain a stable pH gradient.…”
Section: Mechanism Of Action Of Ampsmentioning
confidence: 99%
“…Study related to clavanin A has demonstrated different activities regarding this peptide, including important points for dentistry, such as antibiofilm and antimicrobial activity. HDP clavanin A showed antibiofilm activity against fungal biofilms when used to coat an amniotic membrane, which is frequently used in ophthalmologic surgery for rapid ocular surface reconstruction 20 . HDPs clavanin A, clavanin MO and LL-37 did not show any degree of cytotoxicity to RAW cells.…”
Section: Discussionmentioning
confidence: 99%
“…The spectra of the dried specimens were recorded on a Shimadzu 8400 FTIR spectrophotometer. Absorbance spectra were recorded from 4,000 to 400 nm with a 4 cm -1 resolution, after subtracting absorbance background (Mandal et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…For SEM images of the self-assembled curd-peptide-based hydrogel, 5 ml of stock solution (10 mg ml -1 ) was placed on the glass coverslip and dried under room temperature. Samples were fixed onto a graphite stub and kept in an auto sputter coater (E5200, Bio-Rad, Hadapsar, Pune, India) under low vacuum for gold coating up to 120 s. Surface morphology was analyzed by a scanning electron microscope (JEOL JSM 5800, GenTech Scientific, NY, United States) operated with an accelerated voltage between 5 and 20 kV (Mandal et al, 2017).…”
Section: Methodsmentioning
confidence: 99%